Manufacturing cell Physical model applied to a study case - Guerrero, John Alexander; López Mesa, Diana Jimena; Benachí , Ermilso Díaz (I+ T+ C- Research, Technology and Science, 2016)
This article shows the physical modeling of a manufacturing cell leading to implementation, referenced to a case study in the welding stage of the chassis production process of luminaires. The physical model is designed by collecting information from the academic field concerning design methodologies and procedures used in the area of cell manufacturing and group technology. Taking such methodologies as reference, a process is generated to obtain a physical model of a manufacturing cell in any of its configurations. Once the process is done, it is used as a general guide for the possible scenarios of manufacturing cells for the case study.